2008
DOI: 10.1021/jo801397g
|View full text |Cite
|
Sign up to set email alerts
|

Chlorination Increases the Persistence of Semiquinone Free Radicals Derived from Polychlorinated Biphenyl Hydroquinones and Quinones

Abstract: Polychlorinated biphenyls (PCBs) comprise a group of persistent organic pollutants that differ significantly in their physicochemical properties, their persistence, and their biological activities. They can be metabolized via hydroxylated and dihydroxylated metabolites to PCB quinone intermediates. We have recently demonstrated that both dihydroxy PCBs and PCB quinones can form semiquinone radicals (SQ •− ) in vitro. These semiquinone radicals are reactive intermediates that have been implicated in the toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
60
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 45 publications
(131 reference statements)
11
60
0
Order By: Relevance
“…Although all attempts to characterize the electrochemical properties of 1 by CV resulted in rapid decomposition, reaction of 1 with a stoichiometric quantity of CoCp 2 in THF afforded a compound that exhibited a sharp, isotropic EPR signal at g = 2.008 (Figure 6 A). [105] This value is consistent with those of other semiquinone radical anionic species [106,107] and the signal for 1 À matched a simulated isotropic spectrum centered at g = 2.008 (Figure 6 B). The absence of hyperfine coupling indicated that the spin density was localized primarily on the quinone moiety and leads us to suggest that reduction of the QBI linker in complexes 2-5 could increase the overall electron-donating ability of 1 without significantly altering the electronic topology of the NHC sites.…”
supporting
confidence: 83%
“…Although all attempts to characterize the electrochemical properties of 1 by CV resulted in rapid decomposition, reaction of 1 with a stoichiometric quantity of CoCp 2 in THF afforded a compound that exhibited a sharp, isotropic EPR signal at g = 2.008 (Figure 6 A). [105] This value is consistent with those of other semiquinone radical anionic species [106,107] and the signal for 1 À matched a simulated isotropic spectrum centered at g = 2.008 (Figure 6 B). The absence of hyperfine coupling indicated that the spin density was localized primarily on the quinone moiety and leads us to suggest that reduction of the QBI linker in complexes 2-5 could increase the overall electron-donating ability of 1 without significantly altering the electronic topology of the NHC sites.…”
supporting
confidence: 83%
“…We have previously shown that the greater the number of chlorines on the oxygenated ring, the more persistent the resulting semiquinone radical (26). Chlorines on the quinone ring should increase the overall electrophilic character of the quinone ring and thereby increase the ease of Michael addition of nucleophiles such as glutathione.…”
Section: Resultsmentioning
confidence: 99%
“…However, for 2,5-dichloro-1,4-benzoquinone these potentials are more positive, ϩ470 and ϩ620 mV (16); for 2,3,5,6-tetrachloro-1,4-benzoquinone (chloranil) these potentials increase to ϩ650 and ϩ726 mV. Semiquinone radicals having a higher degree of chlorination are more persistent (26); thus, production of O 2…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCB29-pQ was synthesized and characterized as previously described (59). Stock solution (50 mM) of PCB29-pQ was prepared in dimethyl sulfoxide (DMSO) before use.…”
Section: Methodsmentioning
confidence: 99%